Microbial Photoinactivation by Visible Light Results in Limited Loss of Membrane Integrity - Katharina Hoenes; Richard Bauer; Barbara Spellerberg; Martin Hessling (MDPI AG, 2021)
Interest in visible light irradiation as a microbial inactivation method has widely increased due to multiple possible applications. Resistance development is considered unlikely, because of the multi-target mechanism, based on the induction of reactive oxygen species by wavelength specific photosensitizers. However, the affected targets are still not completely identified. We investigated membrane integrity with the fluorescence staining kit LIVE/DEAD® BacLight™ on a Gram positive and a Gram negative bacterial species, irradiating Staphylococcus carnosus and Pseudomonas fluorescens with 405 nm and 450 nm. To exclude the generation of viable but nonculturable (VBNC) bacterial cells, we applied an ATP test, measuring the loss of vitality. Pronounced uptake of propidium iodide was only observed in Pseudomonas fluorescens at 405 nm. Transmission electron micrographs revealed no obvious differences between irradiated samples and controls, especially no indication of an increased bacterial cell lysis could be observed. Based on our results and previous literature, we suggest that visible light photoinactivation does not lead to rapid bacterial cell lysis or disruption. However, functional loss of membrane integrity due to depolarization or inactivation of membrane proteins may occur. Decomposition of the bacterial envelope following cell death might be responsible for observations of intracellular component leakage.